2020
DOI: 10.3390/pr8101241
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Transient Characteristics of the Centrifugal Pump during the Startup Period with Assisted Valve

Abstract: The startup period, one of several transient operations in a centrifugal pump, takes note of some problems with these devices. Sometimes a transient high pressure and high flow rate over a very short period of time are required at the startup process. The pump’s dynamic response is delayed because of the rotational inertia of the pump and motor. Our research focuses on how to get a large flow in a short time when the pump cannot meet the requirements alone without a large power driver. To achieve a strong resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Building upon this foundation, more scholars have focused on the flow patterns and noise generation mechanisms within the pump, and have discovered that unsteady flow separation on the suction side of the blades and periodic pressure fluctuations on the blade surface are the main source for noise generation (Choi et al, 2003). Li et al have identified hydraulic imbalance and blade-dynamic interference as the main causes of shaft vibration by studying the unsteady pressure fluctuation characteristics and axial trajectories of mixed-flow pumps (Li et al, 2018a;Li et al, 2020a). Wang et al have improved the stability of pumps and reduced noise by studying the relationship between pressure fluctuation, vibration, and noise in multi-stage pumps (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Building upon this foundation, more scholars have focused on the flow patterns and noise generation mechanisms within the pump, and have discovered that unsteady flow separation on the suction side of the blades and periodic pressure fluctuations on the blade surface are the main source for noise generation (Choi et al, 2003). Li et al have identified hydraulic imbalance and blade-dynamic interference as the main causes of shaft vibration by studying the unsteady pressure fluctuation characteristics and axial trajectories of mixed-flow pumps (Li et al, 2018a;Li et al, 2020a). Wang et al have improved the stability of pumps and reduced noise by studying the relationship between pressure fluctuation, vibration, and noise in multi-stage pumps (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…During the daily operation of the mixed-flow pump, transient events inevitably occur, such as the influence of valves on fluid performance (Li et al. , 2020a, b, c) rapid start-stop operations (Yang et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dai et al [16] proposed three novel transcritical CO 2 high-temperature heat pump systems to recover waste heat. Besides, in recent years, research on the starting of a multistage centrifugal pump [17] and a centrifugal pump with assisted valve [18] has also made some progress.…”
Section: Introductionmentioning
confidence: 99%
“…In this era background, more and more scholars at home and abroad focus on the experiment and research of centrifugal pumps. Zou et al [4], Li et al [5], and Yun et al [6] all researched with the centrifugal pump during the startup process, obtaining the evolution features of the internal flow field and analyzing some fluid phenomena, which can provide some reference for the research of prototype pump's startup period. As a mechanical device of energy conversion and fluid transportation, rotor-stator interaction (RSI) is the main factor of vibration and noise in a centrifugal pump.…”
Section: Introductionmentioning
confidence: 99%